Satellite polarimetric radar image processing - Jia, Jingqi (2019)
In this project, satellite image are collected by Polarimetric Synthetic Aperture Radar (PolSAR). PolSAR is a very powerful tool to differentiate various natural features. The use of radar sensing is operationally advantageous due to the propagational characteristics of microwaves. It is can endure harsh weather conditions and is capable to penetrate materials of the media regardless of precipitation cover. PolSAR data has practical purposes in many areas and several studies have been conducted on the use of Polarimetric data for land cover identification Optical and Radar images cover two distinct aspects in satellite image processing. The former provides more semantic information derived, for example from a wider range of data spectrum. On the other hand, the latter is more versatile as it does not depend on cloudy and night scenes. The purpose of remote sensors is to collect data and it is done by sensing the energy that is reflected from Earth. These sensors could be on satellites or mounted on airplane. Remote sensing provides a variety of uses in vast areas; for example, disaster assessment, natural resource management, sea applications and coastal applications.